2006
DOI: 10.1093/gerona/61.9.918
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Association of Apolipoprotein E and Angiotensin-Converting Enzyme Gene Polymorphisms With Healthy Aging and Longevity: A Population-Based Study From Southern Italy

Abstract: We investigated the association of sex and age with the occurrence of apolipoprotein E (apoE) and angiotensin-converting enzyme (ACE) genotypes in healthy aging and longevity in 1344 healthy individuals and 64 centenarians. As compared to participants younger than 60 years, a significant higher frequency of the apoE/epsilon2 was observed in men aged 60-90 years (p <.001) and in centenarians (p <.001). Logistic regression analysis confirmed this outcome in both participants aged 60-90 years (odds ratio [OR] = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 31 publications
4
49
1
3
Order By: Relevance
“…The ε4-allele frequency in our Spanish (10%) and Italian (8%) young controls was relatively higher than that previously reported by Lewis and Brunner (2004) in Southern Europe. Whereas, the ApoE ε4-allele frequency in Spanish and Italian centenarians was 4.9 and 3.2% respectively, which is within the range of previously published frequencies (1-10%) for European centenarians (Blanche et al, 2001;Capurso et al, 2004;Castro et al, 1999;Gerdes et al, 2000;Louhija et al, 1994;Maruszak et al, 2012;Panza et al, 1999;Panza et al, 2003;Schachter et al, 1994;Seripa et al, 2006). On the other hand, allele frequencies in the Japanese centenarians studied here (ε2 = 7.3%; ε3 = 88.1%; ε4 = 4.6%) are comparable to those previously reported in centenarians of the same country, e.g., ε2 = 4.5%; ε3 = 90.9%; ε4 = 4.5% (Asada et al 1996).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The ε4-allele frequency in our Spanish (10%) and Italian (8%) young controls was relatively higher than that previously reported by Lewis and Brunner (2004) in Southern Europe. Whereas, the ApoE ε4-allele frequency in Spanish and Italian centenarians was 4.9 and 3.2% respectively, which is within the range of previously published frequencies (1-10%) for European centenarians (Blanche et al, 2001;Capurso et al, 2004;Castro et al, 1999;Gerdes et al, 2000;Louhija et al, 1994;Maruszak et al, 2012;Panza et al, 1999;Panza et al, 2003;Schachter et al, 1994;Seripa et al, 2006). On the other hand, allele frequencies in the Japanese centenarians studied here (ε2 = 7.3%; ε3 = 88.1%; ε4 = 4.6%) are comparable to those previously reported in centenarians of the same country, e.g., ε2 = 4.5%; ε3 = 90.9%; ε4 = 4.5% (Asada et al 1996).…”
Section: Discussionsupporting
confidence: 85%
“…The explanation for our novel finding, i.e., that the ε2-allele could benefit EL in the Italian and Japanese population, and specifically favor healthy attainment of EL in the Italian cohort, is less apparent and warrants further research. The ApoE ε2-allele has previously been reported to be more frequent in centenarians (Blanche et al, 2001;Louhija et al, 1994;Schachter et al, 1994;Seripa et al, 2006) than in younger people, but others found no differences (Asada et al, 1996;Capurso et al, 2004;Feng et al, 2011;Louhija et al, 2001;Panza et al, 1999). A meta-analysis considering only studies of centenarians published before 2004 gave a point estimate of 1.50 (95%CI, 1.27-1.78) for ε2-allele frequency in centenarians vs. younger controls (Lewis and Brunner, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, two loci that are repeatedly found by GWAS of aging are APOE (Deelen et al, 2011; Ewbank, 2007; Gerdes, Jeune, Ranberg, Nybo, & Vaupel, 2000) and FOXO3A (Anselmi et al, 2009; Flachsbart et al, 2009; Li et al, 2009; Pawlikowska et al, 2009; Willcox et al, 2008). Similar to AD, APOE ε2 is found to be enriched in elderly and centenarians compared to younger individuals (Seripa et al, 2006). Elder APOE ε2 carriers were found to have reduced accumulation of amyloid pathology via multimodal neuroimaging (Grothe et al, 2017).…”
Section: Molecular Links Between Aging and Admentioning
confidence: 99%
“…Nuestros resultados son similares a aquellos trabajos que mostraron una relación entre la longevidad y el genotipo de ACE (34)(35)(36), siendo el alelo D favorable en cuanto a longevidad. En su estudio, Kritchevsky y cols.…”
Section: Discussionunclassified